Análise de condições de imagem na migração reversa no tempo . - ALCÂNTARA, Mailton Rian Mota (2019)
The time reversal property of two way wave equations is the base of several imaging methods in exploration seismology and medicine. The mathematical formulation of time reversal for acoustic media are revisited and applied to an asymptotic analysis of reverse time migration (RTM), using imaging condition of crosscorrelation type and the method of stationary phase. Alternative imaging conditions are proposed to improve amplitude recovery in RTM. Numerical experiments evaluate the sensitivity of the proposed imaging conditions and focalization of RTM to perturbations to perturbations on the velocity model.